Toward Conceptual Clarity: Out-of-Hospital Birth Practices and Freebirth Entrepreneurialism - Johnston, Krista; MacDougall, Christiana (Atlantis, 2026)
There is a growing interest in giving birth outside of hospitals and healthcare systems. In our analysis of more than five years of qualitative research, we have noted the conflation of unregulated birth care with regulated midwifery care, a concern also identified by several professional midwifery associations in Canada. This is particularly concerning in a national context where midwifery remains insufficiently integrated and understood. Growing healthcare dis/misinformation and increasing politicization around healthcare have led to confusion for those choosing among different forms of birth care. In this article we differentiate among birth workers and practices, focusing on unregulated forms of care, including doulas, lay or traditional midwives, and other kinds of birth workers, as well as freebirth, or unassisted birth. This analysis paper provides information on the range of practices that healthcare providers may encounter and articulates areas of difference and overlap among forms of birth care. It also highlights strategies to address some of the unmet needs that are leading people to choose unregulated birth care.